Mechanochemical synthesis of mesoporous tin oxide: a new generation nanosorbent for 68Ge/68Ga generator technology. Issue 34 (2nd August 2016) - Chakravarty, Rubel; Chakraborty, Sudipta; Shukla, Rakesh; Bahadur, Jitendra; Ram, Ramu; Mazumder, Subhasish; Dev Sarma, Haladhar; Tyagi, Avesh Kumar; Dash, Ashutosh
Abstract : Mesoporous tin oxide nanoparticles were synthesized by a solid-state mechanochemical route for use as a sorbent in a 68 Ge/ 68 Ga generator. Abstract : The present article reports the synthesis and characterization of mesoporous tin oxide (MTO) nanoparticles by a solid-state mechanochemical route. The synthesized material was used as an advanced sorbent material for 68 Ge/ 68 Ga radionuclide generator technology. Gallium-68 ( t ½ = 68 min) obtained from the 68 Ge/ 68 Ga generator is an important diagnostic radioisotope which holds tremendous potential in the non-invasive monitoring of various diseases, including cancer, using positron emission tomography (PET). The crystallite size of the MTO nanoparticles was in the range of 6–12 nm with a large surface area of 265 ± 16 m 2 g −1, while the mean pore radius was found to be 2.1 ± 0.6 nm. Determination of the zeta-potential of the MTO nanoparticles dispersed in solutions at different pH values aided in understanding the sorption and separation mechanisms, which were based on the surface charge developed on the nanosorbent. The sorption capacity observed under column-flow conditions was 85 ± 5 mg Ge per g of nanosorbent. A clinical-scale 68 Ge/ 68 Ga generator (740 MBq) was developed using this nanosorbent. Gallium-68 could be regularly eluted from this generator over a prolonged period of 1 year with >70% elution yield and met all the requirements for clinical use. The suitability of 68 Ga obtained from it was evaluated in preclinical settings by the preparation of a 68 Ga-labeled peptide containing the arginine-glycine-aspartic acid (RGD) motif. To the best of our knowledge, this is the first report on the synthesis of MTO nanoparticles by a mechanochemical route which could be effectively utilized for the routine preparation of clinical-scale 68 Ge/ 68 Ga generators. The promising results obtained in this study would facilitate greater implementation of mechanochemistry for the synthesis of nanosorbents for radionuclide generator technology since this method is simple, economical and convenient.